Use of device-assisted enteroscopy in small bowel disease: an expert consensus statement by the Korean Association for the Study of Intestinal Diseases - Han Hee Lee; Jin Su Kim; Hyeon Jeong Goong; Shin Hee Lee; Eun Hye Oh; Jihye Park; Min Cheol Kim; Kwangwoo Nam; Young Joo Yang; Tae Jun Kim; Seung-Joo Nam; Hee Seok Moon; et al. (Intestinal Research, 2023)
The introduction of device-assisted enteroscopy (DAE) in the beginning of 21st century has revolutionized the diagnosis and treatment of diseases of the small intestine. In contrast to capsule endoscopy, the other main diagnostic modality of the small bowel diseases, DAE has the unique advantages of observing the region of interest in detail and enabling tissue acquisition and therapeutic intervention. As DAE becomes an essential procedure in daily clinical practice, there is an increasing need for correct guidelines on when and how to perform it and what technical factors should be considered. In response to these needs, the Korean Association for the Study of Intestinal Diseases developed an expert consensus statement on the performance of DAE by reviewing the current evidence. This expert consensus statement particularly focuses on the indications, choice of insertion route, therapeutic intervention, complications, and relevant technical points.